Sosialisasi dan Demonstrasi Paving Block dari Sampah Plastik: Potensi Keberlanjutan di Desa Pangkalan Batang Barat - Warman, Aditya; Putri, Indri Emiliana; Faheema, Tengku Alya; Nugraha, Farid Bimo; Elsyukri, Erindavia; Menzano, Farhan; Fatiha, Ayudia; Nadeak, Luga Riela; Apriliant, Daniel; Fadhilah, Raisa Aurel (Yayasan Daarul Huda Kruengmane, 2024)
This socialization and demonstration program evaluates the implementation of paving block making from plastic waste in Pangkalan Batang Barat Village as an innovative solution to the problem of waste management that is often done through burning, resulting in environmental and health impacts. These Riau University student work program aims to reduce the accumulation of plastic waste, increase community understanding of more environmental friendly waste management methods, and create sustainable economic opportunities. The methods used include technical training in the form of socialization and demonstration of the process of making paving blocks involving a mixture of recycled plastic, sand, and oil, as well as mentoring during the production process. Evaluation was conducted using surveys to assess changes in knowledge, skills, and economic impact of the program. The evaluation results showed significant improvements in the community's understanding of waste management, the creation of new jobs, as well as the potential for increased village income through management by Village-Owned +Enterprises (BUMDes). This service indicates that making paving blocks from plastic waste is an effective approach to sustainably manage plastic waste and support local economic development.